Neurocognitive and familial moderators of psychiatric risk in velocardiofacial (22q11.2 deletion) syndrome: a longitudinal study. Issue 8 (14th November 2014) - Kates, W. R.; Russo, N.; Wood, W. M.; Antshel, K. M.; Faraone, S. V.; Fremont, W. P.
Abstract : Background: Although risk for psychosis in velocardiofacial (22q11.2 deletion) syndrome (VCFS) is well established, the cognitive and familial factors that moderate that risk are poorly understood. Method: A total of 75 youth with VCFS were assessed at three time points, at 3-year intervals. Time 1 (T1) psychiatric risk was assessed with the Behavior Assessment System for Children (BASC). Data reduction of BASC scores yielded avoidance–anxiety and dysregulation factors. Time 2 (T2) neuropsychological and family function and time 3 (T3) prodromal/overt psychosis were assessed. Poisson regression models tested associations between T3 positive prodromal symptoms/overt psychosis and T1 psychiatric risk, T2 cognitive and familial factors, and their interactions. Results: T1 avoidance–anxiety ratings predicted T3 prodromal/overt psychosis. T2 verbal learning scores moderated this association, such that individuals with low avoidance–anxiety scores and stronger verbal learning skills were the least likely to demonstrate prodromal/overt psychosis at T3. Low scores on a T2 visual vigilance task also predicted T3 prodromal/overt psychosis, independently of the effect of T1 avoidance–anxiety scores. T1 dysregulation scores did not predict T3 prodromal/overt psychosis in a linear manner. Instead, the association between dysregulation and prodromal/overt psychosis was amplified by T2 levels of family organization, such that individuals with low dysregulation scores and low family organization scores were the most likely to exhibit T3 prodromal/overt psychosis. Conclusions: Significant moderators of psychiatric risk in VCFS include verbal learning skills as well as levels of family organization, carrying implications for early identification and preventative treatment of youth with VCFS at highest risk for psychosis.